State policing in sub-Saharan Africa: the weakest link of security sector governance - Diallo, Fatoumata Sira (Diplomacy and strategy. English series, 2019)
"The key argument of this book is that state policing plays a vital role in the realm of security sector governance, but that African police have several failings that are direct outcomes of their historical development : they are often violent, brutal, corrupt and politicised. As institutions, Africa's national police forces still tend to resemble those established by colonial powers in their structure and conduct, and are typically mistrusted by the very people for whom they are meant to ensure security and safety. When police in Africa fail to execute their mandate properly, the entire security system is eroded and public security is in peril. To fully play their role, state police need to be reformed, adapted, reconstructed, and guided by a new philosophy with human security at its core, to bring an appropriate response to assure citizens' security and safety. This book, adapted from the author's Ph.D. thesis, discusses the challenge."-- Back cover